Плагіни для обробки звуку в Logic Pro - Федченко, І. M. (ХНУРЕ, 2025)
Audio processing is an essential part of modern music production and sound design. Logic Pro is one of the most popular digital audio workstations (DAWs) that offers a wide range of tools for audio processing. In Logic Pro, users can use both built-in and third-party plug-ins for mixing, mastering, and creating sound effects.
Keywords: Плагіни для обробки звуку в Logic Pro